Ribociclib in the treatment of HR+ HER2-negative metastatic breast cancer: updated results from the randomized clinical trials and their role in the clinical practice - I. V. Kolyadina (Opuholi Ženskoj Reproduktivnoj Sistemy, 2021)
The luminal HER2-negative subtype is the dominant variant of metastatic breast cancer; modern combined endocrine therapy with CDK4/6 inhibitors due to significantly change the prognosis of the disease, not only for increasing progression free survival, but also for significantly prolonging the life expectancy of patients. This review presents the features of the mechanism of action of CDK4/6 inhibitors, the most significant and updated results of large, randomized trials with ribociclib (MONALEESA-2, MONALEESA-3, and MONALEESA-7) assessing the efficacy and safety of combined endocrine therapy with various endocrine partners in a population of premenopausal women and menopausal patients. The prospects for the use of CDK4/6 inhibitors for therapy patients with visceral crisis are shown.